The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1038/bjc.1998.376
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen reduces plasma homocysteine levels in healthy women

Abstract: Summary Treatment with tamoxifen is associated with reduced incidence of myocardial infarction. As plasma homocysteine is an independent risk factor for cardiovascular disease, we studied the effects of tamoxifen on plasma homocysteine in 66 healthy women participating in the Italian prevention trial of breast cancer who were randomized in a double-blind manner to tamoxifen 20 mg day-' or placebo for 5 years. They were aged between 35 and 70 years, had undergone previous hysterectomy for non-malignant conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 28 publications
3
16
0
Order By: Relevance
“…In agreement with previous reports [9,10], we observed that tamoxifen therapy was associated with the lowering of serum homocysteine levels, but these changes were not significant. Although the number of our study subjects was small, from our results, we might surmise that tamoxifen treatment does not significantly influence serum homocysteine levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous reports [9,10], we observed that tamoxifen therapy was associated with the lowering of serum homocysteine levels, but these changes were not significant. Although the number of our study subjects was small, from our results, we might surmise that tamoxifen treatment does not significantly influence serum homocysteine levels.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the results have been conflicting, and important alterations have not been identified [7][8][9][10]. Previously, we indicated that the risk of TE during tamoxifen therapy was increased in breast cancer patients with factor V Leiden mutation [11].…”
Section: Discussionmentioning
confidence: 97%
“…Possible mechanisms include the effect of SERMs on lipids, vascular endothelium, insulin-like growth factor-I, and homocysteine. [25][26][27][28][29] For two reasons, women with a history of breast carcinoma may be at a lower risk of developing CHD than women without a history of breast carcinoma. First, estrogens may be etiologic in the development of breast carcinoma and protective of CHD.…”
mentioning
confidence: 99%
“…6 Tamoxifen has several favorable antiatherosclerotic properties. [7][8][9][10][11] Data from several breast cancer trials, [12][13][14] but not all, 15 have suggested that tamoxifen may reduce cardiac events in women.…”
mentioning
confidence: 99%